Biofertilizer based on halotolerant microorganisms promotes the growth of rice plants and alleviates the effects of saline stress - Shan, Shiping; Wei, Zhongwei; Cheng, Wei; Du, Dongxia; Zheng, Dianfeng; Ma, Guohui (Frontiers in Microbiology, 2023)
Long-term soil salinization easily contributes to soil hardness, soil nutrients imbalance and soil microbial diversity reduction, resulting in low rice yield in salinized field, and microbial remediation is one of the important measures to improve salinized soil. This study, on the basis of saline-tolerant compound microbial fertilizer significantly alleviating rice growth stress and increasing rice yield in salinized field, discussed the effects of compound microbial fertilizer on rhizosphere soil microbial diversity and community structure in salinized field, analysed the correlation between the formation of microbial community structure and soil available nutrient factors and as a result, revealed the microbiological mechanisms of saline-tolerant compound microbial fertilizer alleviating rice plant growth stress and increasing nutrients supplying capacity of soil in salinized field. The result, in comparison with using inorganic fertilizer (referred as CK), showed that, notably increased soil available nitrogen, available phosphorus, available potassium and rice paddy yield (p < 0.05) and significantly decreased soil salt content (p < 0.05) were achieved via compound microbial fertilizer (referred as G2). Additionally, the applying of compound microbial fertilizer contributes to the increase in soil microbial diversity and reorganization of microbial community structure, and through the analysis of linear discriminant analysis effect size, a notable difference of relative abundance was found in 13 genera, 6 families and 3 orders between control group and experimental groups (p < 0.05), and by linear discriminant analysis, Desulfomonas was further identified as the differentiated indicator. The redundancy analysis showed that available phosphorus and cation exchange capacity were the key environmental factors that affected microbial community structure. Through bacteria functional prediction, increased rhizosphere soil bacterial metabolism, enzyme activity, membrane transport and other potential functions were achieved by applying compound microbial fertilizer. These findings provide theoretical support to soil microbial improving technology in salinized field.